2022
DOI: 10.5902/1980509850295
|View full text |Cite
|
Sign up to set email alerts
|

Performance da madeira de <i>Acacia mearnsii</i> De Wild para polpação kraft

Abstract: O crescente interesse mundial na polpa celulósica produzida a partir da madeira de Acacia mearnsii incentiva estudos que comprovem sua propensão e eficiência para esse fim. Dessa forma, o objetivo deste estudo foi avaliar as propriedades físico-químicas da madeira de Acacia mearnsii, bem como avaliar seu desempenho na produção de celulose kraft, sob diferentes condições de cozimento. Amostras de madeiras das áreas de produção de sementes (APS) e clones foram avaliados. A polpação kraft foi realizada com fator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Lignocellulosic biomass with high acetyl groups (determined here as acetates) will lead to higher consumption of reagents upon their hydrolyzation in an alkaline medium [30]. The high glucose and xylose (the latter two-times higher than previously observed) [31] and low lignin contents (with low Klason lignin 18.3%) show good perspectives for the pulping of A. mearnsii. A. longifolia, on the other end, showed the exact opposite, with higher lignin and lower polysaccharide contents than the remaining Acacia species.…”
Section: Wood Chemical Compositionmentioning
confidence: 84%
See 1 more Smart Citation
“…Lignocellulosic biomass with high acetyl groups (determined here as acetates) will lead to higher consumption of reagents upon their hydrolyzation in an alkaline medium [30]. The high glucose and xylose (the latter two-times higher than previously observed) [31] and low lignin contents (with low Klason lignin 18.3%) show good perspectives for the pulping of A. mearnsii. A. longifolia, on the other end, showed the exact opposite, with higher lignin and lower polysaccharide contents than the remaining Acacia species.…”
Section: Wood Chemical Compositionmentioning
confidence: 84%
“…Similar results were presented previously for A dealbata and A. melanoxylon wood [13,18,19], with pulp yields above 50% and Kappa numbers below 17. Being widely planted in Brazil, mostly for bark tannin production, the wood of A. mearnsii has also been tested for pulp production, with pulp yields (57%-47%) and Kappa numbers (all below 17%) presented for a vast active alkali range [31]. To the best of our knowledge, no previous pulping study for A. saligna and A. longifolia woods was found.…”
Section: Kraft Pulping Experimental Design and Optimizationmentioning
confidence: 99%
“…The contents of extractives for ST raw material are the highest of the other lignocellulosic materials; empty fruit bunch (EFB) raw material (5.9%), sugarcane bagasse (SB) raw material (2.0%), and Acacia mangium wild wood (6.7%) as plantation hardwoods for a resource of paper production [19]. c Acacia mangium wild [19] The chemical composition of ST is compared to other tree lignocellulosic materials such empty fruit bunches (EFB) [8], sugarcane bagasse as a biomass resource for agricultural waste [7], and Acacia mearnsii wood as a plantation hardwood for papermaking [19]. With a high cellulose percentage of 58.1%, the comparison revealed that ST is a resource with a lot of potential.…”
Section: Resultsmentioning
confidence: 99%
“…Acacia mearnsii wood, due to its basic density of approximately 0.544 g/cm 3 and low lignin content, can produce pulps with high yield and easy bleachability, being indicated for the production of tissue paper, partly, because it presents anatomical elements with lower mechanical strength when compared to Eucalyptus genus woods (GIESBRECHT et al, 2022;SANTOS et al, 2005).…”
Section: Introductionmentioning
confidence: 99%